قياس مستوى الوظائف الإدارية لدى موظفي معاهد علوم وتقنيات النشاطات البدنية - محمدي عبد الوهاب; حنة الهاشمي (My University, 2021)
لقد هدفت هاته الدراسة للتعرف على مستوى الوضائف الإدارية الخمسة لدى موظفي معهد علوم وتقنيات الأنشطة البدنية والرياضية بالأغواط، وطذلك مدى دور هاته الوضائف التخطيط التنظيم التوجيه الرقابةعلى المؤسسات الإداريةودورها في التحقيق والوصول للاهداف المنشودة والمخطط لها من طرف أفراد المنشئة
دراسة على مستوى معهد علوم وتقنيات النشاطات البدنية والرياضية بالأغواط
This study aimed to identify the level of the five administrative positions among the employees of the Institute of Science and Technology of Physical Activities and Sports in Laghouat, as well as to know the extent of the impact of these jobs on administrative institutions and their role in achieving and reaching the goals planned by the individuals of the facility.